Differences in the characteristics of long-term contraceptive device acceptors compared to short-term ones - Ekwanda, M. Frando Ghiffari; Marlina, Uning; Primadina, Nova (Gaceta Médica de Caracas, 2021)
Introduction: Long-term contraception is expected to reduce the Total Fertility Rate. However, currently, the use of short-term contraception is more dominant than the long-term (4:1). The study aims to identify differences in the characteristics of sexually active women of reproductive age using long-term versus short-term contraception.